2006
DOI: 10.4067/s0717-65382006000200011
|View full text |Cite
|
Sign up to set email alerts
|

Biología reproductiva de Dosidicus gigas D'Orbigny 1835 (Cephalopoda, Ommastrephidae) en la zona norte-centro de Chile

Abstract: El presente trabajo estudia la biología reproductiva de la jibia o calamar gigante, Dosidicus gigas frente a la costa de Chile central capturados en julio-agosto (invierno) y octubre-noviembre (primavera) de 1993. En 254 hembras (93 de invierno y 161 de primavera) se analizó el estado de madurez microscópico, determinándose un predominio de hembras en maduración, y en menor porcentaje a punto de desovar. El índice gonadosomático (IGS) y el índice del peso del complejo oviductual (IPCO) indicaron que las hembra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 5 publications
(11 reference statements)
0
8
1
4
Order By: Relevance
“…) to small sizes that prevailed in the HCS since at least the end of the 1980s (Rubio & Salazar 1992). The fact that only individuals maturing at large sizes have been found in the cooler southern HCS off Chile up until now (González & Chong 2006, Ulloa et al 2006, Ibáñez & Cubillos 2007 further strengthens the hypothesis that size-at-maturity is coupled to water masses, i.e. temperature and nutrient conditions.…”
Section: Discussionmentioning
confidence: 52%
“…) to small sizes that prevailed in the HCS since at least the end of the 1980s (Rubio & Salazar 1992). The fact that only individuals maturing at large sizes have been found in the cooler southern HCS off Chile up until now (González & Chong 2006, Ulloa et al 2006, Ibáñez & Cubillos 2007 further strengthens the hypothesis that size-at-maturity is coupled to water masses, i.e. temperature and nutrient conditions.…”
Section: Discussionmentioning
confidence: 52%
“…5b). This result is consistent with that reported in some studies (González and Chong, 2006;Zúñiga et al, 2008), it contradicts the results reported by Nigmatullin et al (2001). Lack of evidence in this study for the presence of the small-size group described in Nigmatullin et al (2001) might result from the low catchability of small squid by the large jiggers used in this study.…”
Section: Dietscontrasting
confidence: 54%
“…En ambos sexos los valores máximos del IGS se registraron en mayo y septiembre, lo que podría sugerir que estos calamares migrarían durante otoño y primavera hacia aguas oceánicas para completar su maduración y desovar, como se ha propuesto anteriormente (Nesis 1970, Ibáñez & Cubillos 2007, Ibáñez et al 2015. Durante 1993 y 2003, los calamares registraron valores del IGS mayores durante los meses de primavera (Cubillos et al 2004, González & Chong 2006. Estos resultados son concordantes con las épocas de reproducción de la jibia en Chile (Ibáñez et al 2015).…”
Section: Discussionunclassified
“…y verano (octubre-enero) en la zona oceánica (Nesis 1970, González & Chong 2006, Ibáñez & Cubillos 2007, Ibáñez et al 2015. Contrariamente los estudios reproductivos de esta especie en aguas peruanas confirman la ocurrencia de desoves frente a la costa y en la zona oceánica (Tafur & Rabí 1997, Tafur et al 2001.…”
unclassified